Advancing Neuroscience Research in Africa: Invertebrate Species to the Rescue. (15th March 2018) - Balogun, Wasiu Gbolahan; Cobham, Ansa Emmanuel; Amin, Abdulbasit; Seeni, Azman
Highlights: Scientific research is underepresented in Africa. Invertebrates are cost-effective method of developing neuroscience in Africa. We highlight the comparative advantages of invertebrates in neuroscience research. We highlight institutions and organizations currently promoting invertebrate neuroscience in Africa. There is a need for concerted efforts to improve the use of invertebrates in Africa research. Abstract: Neuroscience research and training in many African countries are difficult due to funding and infrastructure deficit. This has resulted in few neuroscientists within Africa. However, invertebrates such as Drosophila and Caenorhabditis elegans could provide the perfect answer to these difficulties. These organisms are cheap, easy to handle and offer a comparable advantage over vertebrates in neuroscience research modeling because they have a simple nervous system and exhibit well-defined behaviors. Studies using invertebrates have helped to understand neurosciences and the complexes associated with it. If Africa wants to catch up with the rest of the world in neuroscience research, it needs to employ this innovative cost-effective approach in its research. To improve invertebrate neuroscience within the Africa continent, the authors advocated the establishment of invertebrate research centers either at regional or national level across Africa. Finally, there is also a need to provide public funding to consolidate the gains that have been made by not-for-profit international organizations over the years.